2017
DOI: 10.1104/pp.17.01572
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-Induced Trophic Shift in an Endosymbiont Dinoflagellate with Physiological and Molecular Consequences

Abstract: Interactions between the dinoflagellate endosymbiont Symbiodinium and its cnidarian hosts (e.g. corals, sea anemones) are the foundation of coral-reef ecosystems. Carbon flow between the partners is a hallmark of this mutualism, but the mechanisms governing this flow and its impact on symbiosis remain poorly understood. We showed previously that although Symbiodinium strain SSB01 can grow photoautotrophically, it can grow mixotrophically or heterotrophically when supplied with Glc, a metabolite normally transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 89 publications
(113 reference statements)
1
44
0
Order By: Relevance
“…Notably, 64% of the putative sugar transporters identified in our transcriptome were not differentially expressed. This corresponds with a study that documented relatively small changes in the expression of glucose transporters after supplementing B. minutum cultures with glucose, which concluded that these sugar transporters are not transcriptionally regulated (Xiang et al, 2018) but likely controlled at the post-transcriptional level, either by RNA editing or by microRNA (Aranda et al, 2013;S. Lin et al, 2015).…”
Section: Algal Sugar Transporterssupporting
confidence: 88%
See 1 more Smart Citation
“…Notably, 64% of the putative sugar transporters identified in our transcriptome were not differentially expressed. This corresponds with a study that documented relatively small changes in the expression of glucose transporters after supplementing B. minutum cultures with glucose, which concluded that these sugar transporters are not transcriptionally regulated (Xiang et al, 2018) but likely controlled at the post-transcriptional level, either by RNA editing or by microRNA (Aranda et al, 2013;S. Lin et al, 2015).…”
Section: Algal Sugar Transporterssupporting
confidence: 88%
“…In plants, they are responsible for efflux and intracellular trafficking of sugars (Deng & Yan, ) and are localized to different cellular compartments (Feng & Frommer, ). SWEETs were previously identified in a B. minutum transcriptome (strain SSB01), and three out of seven transcripts were up‐regulated when the medium was supplemented with glucose (Xiang et al, ). Intriguingly, all but one (which did not pass the prediction probability threshold) of the SWEET transcripts in our transcriptome are predicted to reside in the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…2c). The upregulated transcripts might be those encoding transporters involved in exporting glucose from the endosymbiont to the host 17,18 . Overall, the transcript-level results support the hypothesis that SSB01 is specifically deficient for N in hospite.…”
Section: Resultsmentioning
confidence: 99%
“…Animal Culture and Maintenance. Small sea anemone (Aiptasia) larvae were cultured in the laboratory (21). Larvae were obtained via induced spawning of clonal adult Aiptasia anemone lines CC7 (male) and PLF3 (female) in paired co-culture in artificial sea water (ASW; 34 ppt Coral Pro Salt in deionized (DI) water, pH 8.0, Red Sea Inc.) (9).…”
Section: Methodsmentioning
confidence: 99%